ST. MATTHEW ON A SIDETRACK: THEORIES OF CUMULATIVE ADVANTAGE AND THE BOOK DISSEMINATION OF TWO FINNISH LEARNED SOCIETIES BEFORE WORLD WAR II - LILJA, JOHANNA (Knygotyra, 2010)
The paper deals with the international dissemination of scholarly publications in a peripheral country before World War II. Many studies have indicated that scientific success accumulates to few prominent scholars, institutions and countries, while the actors with modest premises are left on the margins of the scholarly community. Robert Merton called this phenomenon the Matthew effect in science. Some scientists regard this effect as a pathology, whereas others consider it inevitable and advantageous. Merton himself considered that there are some countervailing processes which limit the Matthew effect. The hypothesis of this paper is that in a peripheral country like Finland, the noncommercial distribution of scholarly publications, may have served as one counterforce to the Matthew effect. The focus is on the exchange of publications which was a dominant way of distributing scholarly publications at the time. The development of the exchange relations of two Finnish learned societies indicates that the exchange balanced the competition for scientific success between major and minor countries. The exchange could open contacts with the established scientific centres, but also with young societies in small or peripheral countries. Contacts with the established scientific centres were often not as profitable as those with smaller institutions which concentrated on similar research problems.